THE EFFECTIVENESS OF ANPP AS AN INSTITUTE FOR PROMOTING JUSTICE, EVEN IN THE FACE OF ITS DEPENALIZATION PROPOSAL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The present work aims to analyze the nuances of the Criminal Non-Prosecution Agreement (ANPP) and the way it presents itself, given that this institute, which was approved in our criminal procedure code, is innovative and is in line with practices of consensual justice, practices that are gaining more and more relevance on the national scene. Furthermore, given the decriminalizing nature of the law, the work aims to assess, taking into account both the position of the victim and the accused, whether this institute is capable of responding in a proportionate manner to the desires for justice. of all parties involved. To this end, the literary and jurisprudential review will be used as the main methodology, in addition to the hypothetical-deductive method with the purpose of analyzing how the doctrine, in general, has interpreted this institute and how the jurisprudence has positioned itself in the still controversial aspects of the law.